Does the International Community Have Efforts to Protect the Marine Environment from Seabed Mining? - Idris Idris; Taufik Rachmat Nugraha (Sriwijaya Law Review, 2021)
Through the United Nations, the international community is seriously paying attention to the use of seabed areas as regulated by the Law of the Sea Convention 1982, which states that the area and its resources are the common heritage of humankind.  The 1994 Agreement has implemented chapter XI. The resources are relating to the state's interests in terms of energy exploration and environmental impact aspects. An increasing need for global electronic products by many countries in which of the components are rare minerals. Various minerals such as manganese, polymetallic nodules, and polymetallic sulphur are lying down in the seabed. However, seabed also had an essential role in keeping the marine ecosystem balanced. On the one hand, the human's need for those minerals also cannot be denied. Draft of regulations by the International Seabed Authority to manage deep-sea mining are still insufficient to prevent irrevocable damage to the marine ecosystem and loss of essentials species for the next. On the other hand, the spirit of Sustainable Development Goals 14 concerns life underwater. This paper examines deep-sea mining science from a legal perspective to protect and preserve seabed for the future generation using normative approach describing norms and principles in the Law of the Sea Convention 1982. As a result, the commercialisation of deep-sea mining violates the principle of the convention. Thus, it needs to encourage ISA to enhance the minimum requirements for all contracting parties in the future.